2012
DOI: 10.1177/0899764012461400
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of Nonprofit Organizations with Local Government for Immigrant Language Acquisition

Abstract: This article maintains that local government and nonprofit organizations are key collaborative agents in the delivery of language access services in the City of Philadelphia. Based on research conducted from February 2009 through September 2010, this article utilizes personal interviews, document analyses, and other data to situate the shared responsibility forged between the public and nonprofit sectors in the realm of language access. Local government relies on a range of nonprofit networks for both public s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…First, immigrant nonprofit staff must be versed in one or multiple non-English languages. Second, immigrant-serving nonprofits oftentimes must offer language assistance through interpretation (oral) and/or translation (written documents) (Mulé, 2010), requiring staff to navigate nuances in terminology and culture (Listokin & Listokin, 2001;Wilson, 2013). Third, immigrant-serving nonprofits must become cultural brokers between their communities and local government and mainstream institutions (Wilson, 2013).…”
Section: Creaming Among Immigrant and Nonimmigrant Nonprofitsmentioning
confidence: 99%
“…First, immigrant nonprofit staff must be versed in one or multiple non-English languages. Second, immigrant-serving nonprofits oftentimes must offer language assistance through interpretation (oral) and/or translation (written documents) (Mulé, 2010), requiring staff to navigate nuances in terminology and culture (Listokin & Listokin, 2001;Wilson, 2013). Third, immigrant-serving nonprofits must become cultural brokers between their communities and local government and mainstream institutions (Wilson, 2013).…”
Section: Creaming Among Immigrant and Nonimmigrant Nonprofitsmentioning
confidence: 99%
“…Eng, Liu, and Sekhon (2012) found nonprofits leverage social mission to improve their ability to acquire network resources. Wilson (2013) found local governments implement municipal directives by using their nonprofit networks, and then build network ties with the targeted beneficiary group to implement the service. Kapucu and Demiroz (2013) found that nonprofits participate in network capacity building programs to strengthen network relationships.…”
Section: Open Systemsmentioning
confidence: 99%
“…Although mission statements are viewed as goal setting instruments that nonprofit executives use to direct an organizations' services, recently some nonprofit research has questioned this rational approach arguing that nonprofits are not closed systems but rather open systems embedded in their external environment via social networks that enable and constrain action (Carman & Nesbit, 2013;B. Chen & Graddy, 2010;Kapucu & Demiroz, 2013;Leiter, 2013;Wilson, 2013).…”
mentioning
confidence: 99%
“…Community foundations position themselves as local problem solvers. Foundation-led initiatives bring nonprofits and local governments together on community issues as diverse as immigrant language acquisition (Wilson 2013) and welfare to work partnerships (Stone 2000). Public managers might consider how to strategically partner with community foundations as a way to harness nonprofit resource dependence on philanthropic foundations for public purposes.…”
Section: Findings and Discussionmentioning
confidence: 99%